PENGARUH AIR REBUSAN DAUN HARENDONG BULU (Clidemia hirta) TERHADAP KADAR GULA DARAH MENCIT (Mus musculus) - Okta Malia; Dian Samitra; Eka Lokaria (LP4MK STKIP PGRI Lubuklinggau, 2020)
This study aims to determine the effect of the water boiled leaves of Clidemia hirta on blood sugar levels in Swiss Webster mice (Mus musculus). This research using a completely randomized design research design (CRD) with 5 treatment groups namely; Aquades control group (P0), 3 g sucrose treatment (P1), 3 g sucrose treatment + boiled bristle leaves boiled water at a dose of 0.13 ml/KgBB (P2), 3 g sucrose treatment + boiled bristle leaves boiled water at a dose of 0.26 ml/KgBB (P3), 3 g treatment of sucrose + boiled bristle leaves boiled water at a dose of 0.39 ml/KgBB (P4). Before administration of the extract, mice in the treatment groups P1, P2, P3 & P4 were induced using 3 g of sucrose for 5 days. Then after 5 days for groups P2, P3, and P4 followed by giving boiled water leaves for 7 days. The analysis result of One Way Anova Test shows that Fcount > Ftable (18.86 > 2.51). This shows the boiled water affects the blood sugar levels of male Swiss Webster mice. The concentration of extract at P4 (0.39 ml/KgBB) was more effective in reducing blood sugar levels.